Hadith dalam Perspektif Muhammad Asad - Amir, Ahmad Nabil (Jurnal Ilmiah Al-Mu'ashirah: Media Kajian Al-Qur'an dan Al-Hadits Multi Perspektif, 2022)
The paper analyse the ideas of hadith (prophetic tradition) as espoused by Muhammad Asad (1990-1992) and its significance in contemporary hadith thought. It studies the essential ideas he developed in his discussion of hadith as reflected in his works such as Sahih al-Bukhari The Early Years of Islam; Islam at The Crossroads (chapter â€œHadith and Sunnahâ€ and â€œThe Spirit of the Sunnahâ€); This Law of Ours and Other Essays, The Road to Mecca and The Message of the Qurâ€™an. The influence of hadith was also deeply manifested in his â€œjournalistic monologueâ€ Arafat: A Monthly Critique of Muslim Thought, a periodical he founded in 1946 in Kashmir and other works that addresses significance principles and issues of hadith and essays that incorporate rising themes in contemporary ages, such as â€œSocial and Cultural Realities of the Sunnahâ€. The research was structured based on descriptive, analytical, historical and comparative method. It attempts to analyse the crucial ideas of hadith principles brought forth by Asad and compared these with other critical views set forth of classical Muslim traditionists. The study concluded that Muhammad Asad had significantly contributed to the revival and development of hadith in the modern world with his profound translation and commentary of al-Bukhariâ€™s Sahih â€“ Sahih al-Bukhari The Early Years of Islam - that extensively survey the significant tradition of hadith and its intellectual and historical manifestation over centuries. He also responded to the traditional arguments by historians and orientalists who were sceptical of the historical authenticity of hadith narrative and tradition.ABSTRAKMakalah ini menyorot fikrah hadith Muhammad Asad (1990-1992) dan kontribusinya dalam pemahaman hadith kontemporer. Ia membincangkan kefahaman asas tentang hadith yang dirumuskan dalam karya-karyanya seperti Sahih al-Bukhari The Early Years of Islam; Islam at The Crossroads (bab â€œHadith and Sunnahâ€ dan â€œThe Spirit of the Sunnahâ€); This Law of Ours and Other Essays; The Road to Mecca dan The Message of the Qurâ€™an. Pengaruh hadith ini turut ditinjau daripada artikelnya dalam jurnal Arafat dan makalahnya yang lain terkait tema-tema hadith dan sunnah dan pemahaman serta cabarannya di abad moden, seperti tulisannya â€œSocial and Cultural Realities of the Sunnahâ€. Reka bentuk kajian adalah bersifat deskriptif, analitis, historis dan komparatif. Kajian cuba mengembangkan ide dan fikrah hadith yang dirumuskan Asad dari perspektifnya yang moden dan membandingkannya dengan pemikiran-pemikiran sejarah yang krusial terkait prinsip hadith yang dibawakan oleh pemikir Islam yang lain. Dapatan kajian menyimpulkan bahawa Muhammad Asad telah memberikan sumbangan yang penting dalam pemikiran hadith di abad moden dengan hasil penulisannya yang prolifik dan substantif, termasuk terjemahan dan syarahannya yang ekstensif terhadap Sahih al-Bukhari yang memuatkan komentar-komentar yang baru dan analisis sejarahnya yang mendalam terhadap kitab ini. Ia merumuskan pertentangan-pertentangan hukum dan istinbat-istinbat fuqaha dan muhaddith dalam tradisi syarah hadith yang kritis. Ia turut merespon pertikaian-pertikaian asas yang dibangkitkan oleh golongan orientalis dan intelektual yang skeptis terhadap riwayat-riwayat sejarah dalam tradisi hadith.Â